An analysis of burned human and animal bones: A Case study of the Celtic graves from Brežice (Slovenia) - Hincak, Zdravka (Array, 2014)
An interpretation of cremated bones in the archaeological record presents a real challenge to the bioarchaeologists. The standard osteological procedures created primarily for unburned osteological material often fail to identify this highly fragmented samples transformed by fire. The aim of this study is to present possibilities for identification of human and animal burned bones in the archaeological record. Identification starts with an analysis of thermal destruction patterns visible on the bones and teeth remains. Time, temperature and environment leave a specific colour on the bone which could be observed on different levels. Finally, the results of histological methods with the accent on potentials and limits were presented. This study is a reconstruction and an interpretation of the human and animal osteological remains from sixty eight Celtic graves of the Middle La Tène period from Brežice in Slovenia.